Has the Copayment Ceiling Improved Financial Protection in the Korean National Health Insurance System? Evidence From the 2009 Policy Change - Tae-Jin Lee; Chelim Cheong (Korean Society for Preventive Medicine, 2017)
Objectives To relieve the financial burden faced by households, the Korean National Health Insurance (NHI) system introduced a "copayment ceiling," which evolved into a differential ceiling in 2009, with the copayment ceiling depending on patients' income. This study aimed to examine the effect of the differential copayment ceiling on financial protection and healthcare utilization, particularly focusing on whether its effects varied across different income groups. Methods This study obtained data from the Korea Health Panel. The number of households included in the analysis was 6555 in 2008, 5859 in 2009, 5539 in 2010, and 5372 in 2011. To assess the effects of the differential copayment ceiling on utilization, out-of-pocket (OOP) payments, and catastrophic payments, various random-effects models were applied. Utilization was measured as treatment days, while catastrophic payments were defined as OOP payments exceeding 10% of household income. Among the right-hand side variables were the interaction terms of the new policy with income levels, as well as a set of household characteristics. Results The differential copayment ceiling contributed to increased utilization regardless of income levels both in all patients and in cancer patients. However, the new policy did not seem to reduce significantly the incidence of catastrophic payments among cancer patients, and even increased the incidence among all patients. Conclusions The limited effect of the differential ceiling can be attributed to a high proportion of direct payments for services not covered by the NHI, as well as the relatively small number of households benefiting from the differential ceilings; these considerations warrant a better policy design.